(untitled) (Journal of Parents and Teachers, 2016)
The following article deals with the concept of resilience such as the ability to overcome adversities. It is a psychological concept which is form physics; it helps to human beings to maintain their emotional balance. It suggests some activities in which that concept is working with teachers in different educational situations; everything is proposed as a help and training to the teacher.